Pharmacological MRI to investigate the functional selectivity of 5-HT1A receptor biased agonists. (1st August 2020) - Vidal, Benjamin; Bolbos, Radu; Redouté, Jérôme; Langlois, Jean-Baptiste; Costes, Nicolas; Newman-Tancredi, Adrian; Zimmer, Luc
Abstract: The emerging concept of "biased agonism" denotes the phenomenon whereby agonists can preferentially direct receptor signalling to specific intracellular responses among the different transduction pathways, thus potentially avoiding side effects and improving therapeutic effects. The aim of this study was to investigate biased agonism by using pharmacological magnetic resonance imaging (phMRI). The cerebral blood oxygen level dependent (BOLD) signal changes induced by increasing doses of two serotonin 5-HT1A receptor biased agonists, NLX-112 and NLX-101, were mapped in anaesthetized rats. Although both compounds display high affinity, selectivity and agonist efficacy for 5-HT1A receptors, NLX-101 is known to preferentially activate post-synaptic receptors, whereas NLX-112 targets both pre- and post-synaptic receptors. We used several doses of agonists in order to determine if the regional selectivity of NLX-101 was dose-dependent. NLX-112 and NLX-101 induced different positive and negative hemodynamic changes patterns at equal doses. Importantly, NLX-101 had no significant effect in regions expressing pre-synaptic receptors contrary to NLX-112. NLX-112 also produced higher BOLD changes than NLX-101 in the orbital cortex, the somatosensory cortex, and the magnocellular preoptic nuclei. In other regions such as the retrosplenial cortex and the dorsal thalamus, the drugs had similar effects. In terms of functional connectivity, NLX-112 induced more widespread changes than NLX-101. The present phMRI study demonstrates that two closely-related agonists display notable differences in their hemodynamic "fingerprints". These data support the concept of biased agonism at 5-HT1A receptors and raise the prospect of identifying novel therapeutics which exhibit improved targeting of brain regions implicated in neuropsychiatric disorders. This article is part of the special issue entitled 'Serotonin Research: Crossing Scales and Boundaries'. Highlights: We mapped central effects of two biased agonists of 5-HT1A receptors using fMRI. Previous studies suggest that NLX-101 avoid raphe receptors, contrary to NLX-112. BOLD changes induced by NLX-101 were less widespread than NLX-112 and absent from raphe. NLX-112 produced wider changes in functional connectivity as compared to NLX-101. This non-invasive approach could be applied to study biased agonism in human brain.